El efecto de la atención a noticias en la participación política de los jóvenes en el Área Metropolitana de Monterrey, México. Un estudio longitudinal - Martínez Villarreal, Juan de Dios; Maldonado Maldonado, Lauro (2017)
ABSTRACT This study aims to determine the role of the media in the attention to news as a trigger for the political participation of young people, an essential factor for the development of democracy in the State of Nuevo León. With a longitudinal approach, it applies a quantitative cutoff methodology through two opinion surveys at different times. The most relevant results show that attention to news and policy programs does generate a positive interest in youth in this area, an interest that is expressed in the conventional political participation of young people, but not in the unconventional. Keywords: attention to news and political TV shows, systemic approach, political participation, interest in politics.